Medieval genomes from eastern Iberia illuminate the role of Morisco mass deportations in dismantling a long-standing genetic bridge with North Africa - Gonzalo Oteo-Garcia; Marina Silva; M. George B. Foody; Bobby Yau; Alessandro Fichera; Llorenç Alapont; Pierre Justeau; Simão Rodrigues; Rita Monteiro; Francesca Gandini; María Luisa Rovira Gomar; Albert Ribera i Lacomba; et al. (Genome Biology)
Abstract Background The Islamic influence on the Iberian Peninsula left an enduring cultural and linguistic legacy. However, the demographic impact is less well understood. This study aims to explore the dynamics of gene flow and population structure in eastern Iberia from the early to late medieval period through ancient DNA. Results Our comprehensive genomic analysis uncovers gene flow from various Mediterranean regions into Iberia before the Islamic period, supporting a pre-existing pan-Mediterranean homogenization phenomenon during the Roman Empire. North African ancestry is present but sporadic in late antiquity genomes but becomes consolidated during the Islamic period. We uncover one of the earliest dated Islamic burials in Spain, which shows high levels of consanguinity. For the first time, we also demonstrate the persistence of North African ancestry in a Christian cemetery until the seventeenth century, in addition to evidence of slave trafficking from North Africa. Conclusions This study reveals the complex interaction between political events and cultural shifts that influenced the population of eastern Iberia. It highlights the existence of a slave trade, underscores the low impact of the Reconquista in the genetic landscape, and shows the lasting impact of post-medieval events, such as the Expulsion of the Moriscos in 1609 CE, on the region’s genetic and cultural landscape, through mass population displacement and replacement.